2016
DOI: 10.1007/s40263-016-0366-z
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Safety Warnings on Antipsychotic Drug Prescribing in Elderly Persons with Dementia in the United Kingdom and Italy: A Population-Based Study

Abstract: The 2004 warnings led to a reduction in the use of olanzapine and risperidone and increased the use of quetiapine/conventional APs in both countries. From 2009, the use of APs decreased in persons with dementia in the UK but not in Italy. Possible reasons for the difference in AP use between the two countries include a more proactive approach towards reducing the use of APs in the UK than in Italy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
35
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 23 publications
0
35
0
Order By: Relevance
“…All of the 70 publications included are observational studies based on routinely collected health data, which included health insurance or hospital records. Thus, no RCTs were found for the defined search period.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…All of the 70 publications included are observational studies based on routinely collected health data, which included health insurance or hospital records. Thus, no RCTs were found for the defined search period.…”
Section: Resultsmentioning
confidence: 99%
“…Two publications examined safety warnings for two mutually independent substances each, that is, 70 publications reported 72 studies. If a study contained multiple characteristics, the characteristics of these studies were counted multiple times in the following analyses, for example, studies examining more than one safety warning on one substance or substance group (multiple counts for safety warnings per study) or where a safety warning included multiple recommendations, for example, indication limitations and new adverse reactions (multiple counts for the content of the safety warning) were also subject to multiple counting.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies reported a decrease in AP prescribing [11, 40] while other studies showed an increase or stagnation in AP use [41, 42]. …”
Section: Discussionmentioning
confidence: 99%
“…18 A similar study looking at antipsychotic prescribing in the UK and Italy noted that safety warnings combined with proactive national initiatives in the UK may have contributed to a more sustained reduc tion in prescribing than occurred in Italy. 19 A 2005 study evaluated the quality of a group of direct healthcare profes sional communication letters sent during 2000 and 2001 that were intended to communicate important new drug safety information. 20 This study found a corre lation between the perceived quality of the letter and the extent to which physi cians regarded the new information as important.…”
mentioning
confidence: 99%